Strengthening the Network of Rural Women through the production, processing and marketing of basic grains - Bonilla-Leiva, Alejandra (2012)
This project was able to increase grain production, industrialization and marketing, to have food and nutrition alternatives to strengthen the food security of rural areas. The local impact is expressed in strengthening family income of the people involved in the project, the increase in grain production, industrialization technology transfer, diet improvement and employment generation for women, both in grain production in the field and in food processing. Capacity building in women associated to Rural Women’s Network was possible because of women’s commitment and the continued suppor t of the project. A product based on beans and rice with a high nutritional value was generated, which could be distributed in schools, childcare centers and local suppliers.The regional impact is given in the product introduction with emphasis on children. Then, it will be extended to larger market.